Digital signal processing : theory and practice - Bellanger, Maurice (John Wiley & Sons, Inc., 2024)
"Signal processing is required and deployed in almost all engineering fields, not only electronics and communications but also biology, mechanics, chemistry, and geophysics. Moreover, signal processing algorithms are exploited for data analysis and modelling in business and finance and are also at the core of artificial intelligence systems. Delivering on the promise of theory and practice throughout, the author ensures that the chapters and exercises meet the requirements of both students and industry practitioners, with more advanced topics appearing in the second half of the book. Mathematical concepts are explained, and merge well with the text, allowing the reader to follow the narrative instead of breaking off into tough mathematical diversions. The book has been updated throughout and includes a brand-new section on neural networks. This book series, published originally in French, has not been available in English for many years, and readers will find that it stands alone as a complete text, with no earlier edition knowledge required"-- Provided by publisher.
Translation of: Traitement numérique du signal.
Keywords: Signal processing -- Digital techniques.; elektronické knihy; electronic books